USE OF TACROLIMUS IN CHILDREN FOR TRANSPLANTATION OF KIDNEYS TAKEN FROM LIVE RELATIVE DONORS - V. A. Goryainov; M. M. Kaabak; N. N. Babenko; M. M. Morozova; E. N. Platova; L. I. Agureeva; V. V. Panin; O. V. Dymova (Union of pediatricians of Russia, 2014)
The authors present their experience of immunosuppressive therapy with calcineurin blockers in the post-transplantation period (after living-related kidney transplantation). The study was aimed at determining effect of immunosuppressive drug tacrolimus on results of living-related kidney transplantation in children (group 1). The 58 children, who did not receive tacrolimus in the process of the study, constituted the control group (group 2). The following parameters were used to perform comparative analysis: Kaplan-Meier cumulative survivability of recipients and transplants, Cox cumulative hazard level, log-rank test. Moreover, we calculated the rates of transplanted kidney loss and mortality. Results: survivability of transplants and patients was higher in the main group than in the control group (p < 0.05). Conclusions: thus, results of the performed analysis allow claiming that use of tacrolimus for immunosuppressive therapy positively affects results of the living-related kidney allotransplantation in children.